Socio-psychological patterns in the mass consciousness of the post-Soviet society (first article) - Shamyakina, Tat’yana I. (Journal of the Belarusian State University. Sociology, 2019)
In a controversial, deliberately polemical form, some stable, most universal socio-psychological stereotypes (patterns) of mass consciousness are considered, conditioned by the action of archetypes of the collective unconscious. The reasons for their stability, as well as changes due to certain social circumstances, are established. Examples of various kinds of manipulative technologies are given.